Strategi Digital Marketing Melalui Media Sosial Tiktok Dengan Pendekatan AIDA (Studi Kasus: Lavanya.Wo) - Oky Bakti Wiarso; Hafiz Rayanda Bhakti; Mochamad Amirudin; Chrys Dian Aji Bagus Pamungkas; Ito Setiawan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study analyzes the digital marketing strategy of Lavanya.WO through the TikTok platform using the AIDA model to evaluate how promotional content influences audience engagement and client acquisition. The background of this research stems from the rapid growth of TikTok as a highly visual and interactive platform, making it a strategic medium for promoting wedding organizer services that rely heavily on aesthetics, storytelling, and emotional appeal. The purpose of this study is to examine how each stage of the AIDA modelAttention, Interest, Desire, and Action is reflected in Lavanya.WO’s promotional content and to assess its effectiveness in increasing brand visibility and potential client conversion. This research uses a descriptive qualitative method, with data collected through interviews, observation of TikTok content, documentation, and literature review. The findings indicate that Lavanya.WO successfully applies visual hooks, trending audio, and compelling video openings to attract attention; delivers storytelling and service explanations to build interest; uses testimonials, emotional moments, and decoration showcases to generate desire; and incorporates clear calls-to-action to encourage user engagement and booking inquiries. However, the effectiveness of this strategy is constrained by limited content consistency, creative resources, and an incomplete understanding of TikTok’s algorithm. This study concludes that optimizing content variation, strengthening visual identity, and leveraging TikTok insights can significantly enhance promotional performance. The implications of this research highlight the importance of structured digital marketing strategies for service-based businesses, particularly those operating in visually oriented creative industries such as wedding organizing.